Predictors of Response for “Off” Time Improvement With Levodopa-Carbidopa Intestinal Gel Treatment: An Analysis of the GLORIA Registry - Poewe, Werner; Bergmann, Lars; Robieson, Weining Z.; Antonini, Angelo (Frontiers in Neurology, 2020)
Background: Levodopa-carbidopa intestinal gel (LCIG) is a long-term therapy for motor fluctuations in patients with advanced Parkinson’s disease (PD). The aim of this analysis was to identify the baseline characteristics that predict “Off” time reduction in advanced PD patients treated with LCIG under routine clinical care in the GLORIA registry. Methods: Patients were followed under routine care for 24 months (M) with delivery of LCIG via percutaneous gastrojejunostomy. Analysis of covariance (ANCOVA) and logistic regression were performed to identify baseline characteristics that predict “Off” time reduction. Results: Compared to baseline, 86% (n/N=131/152; mean ± SD baseline “Off” time: 3.4 ± 2.2 hours) of M24 completers had ≥ 1 hour reduction in “Off” time and 64% (n/N=97/152; mean ± SD baseline “Off” time: 7.6 ± 2.9 hours) had ≥ 3 hours “Off” time reduction at M24. Most baseline characteristics were similar across responder subgroups; however, patients with ≥ 3 hours “Off” time improvement had more “Off” time and less time with dyskinesia at baseline compared to patients with < 3 hours “Off” time reduction. Despite having less improvement in absolute “Off” hours at M24, patients with < 3 hours “Off” time reduction experienced a 33% median reduction in “Off” time and a 44% median reduction in dyskinesia at M24, which was similar to the dyskinesia improvement observed among patients with ≥ 3 hours “Off” time improvement (50% median reduction). Baseline “Off” time was both the best predictor of and the only significant factor associated with “Off” time improvement (P < .0001). Conclusions: LCIG treatment led to clinically meaningful improvements in “Off” time in 86% of advanced PD patients and those with greater “Off” time are likely to experience the largest absolute reduction in hours “Off”.